2021
DOI: 10.3390/ma15010290
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Cementitious Composites Incorporating Nano Graphite Platelets as Additive Carbon Material

Abstract: Nano graphite platelets (NGPs) belong to the carbon family and have a huge impact on the construction industry. NGPs are used as multi-functional fillers and have the potential to develop reinforcing within cementitious composites. In this paper, NGPs were incorporated in cementitious composites to investigate the effects of NGPs on the fresh, mechanical, durability, and microstructural properties of concrete. Five mixes were prepared with intrusion of NGPs (0%, 0.5%, 1.5%, 3%, and 5% by weight of cement). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…These increments are in line with other research in which GNP caused a higher bending strength in zirconium [7,45], ultra-high performance concrete [49], self-consolidating cementitious systems [8], concrete with E-waste plastic coarse aggregate [9], geopolymers [10], electrically conductive cementitious composites [11], concrete incorporating an iron-particle contained nanographite by-product [12], and other construction binder-based materials [13][14][15][16][17]. Additionally, the highest bending strength of the mortar composites was observed with the addition of 0.22% GNP, which is also in line with other existing results demonstrating better bending strength properties in highperformance cementitious composites with GNP addition [50]. Other authors evaluated the properties of an aluminum-magnesium-silica combined material modified through hybrid mixing and SiC powder [51].…”
Section: Bending Strengthsupporting
confidence: 87%
See 1 more Smart Citation
“…These increments are in line with other research in which GNP caused a higher bending strength in zirconium [7,45], ultra-high performance concrete [49], self-consolidating cementitious systems [8], concrete with E-waste plastic coarse aggregate [9], geopolymers [10], electrically conductive cementitious composites [11], concrete incorporating an iron-particle contained nanographite by-product [12], and other construction binder-based materials [13][14][15][16][17]. Additionally, the highest bending strength of the mortar composites was observed with the addition of 0.22% GNP, which is also in line with other existing results demonstrating better bending strength properties in highperformance cementitious composites with GNP addition [50]. Other authors evaluated the properties of an aluminum-magnesium-silica combined material modified through hybrid mixing and SiC powder [51].…”
Section: Bending Strengthsupporting
confidence: 87%
“…Buildings 2022, 12, x FOR PEER REVIEW 15 of 21 [50]. Other authors evaluated the properties of an aluminum-magnesium-silica combined material modified through hybrid mixing and SiC powder [51].…”
Section: Mathematical Model For the Prediction Of Bending Strengthmentioning
confidence: 99%
“…Moreover, driven by advanced nanotechnology, nanoscale carbon-based materials have attracted extensive attention due to their high electrical conductivity and multifunctional applications. The admixture of nanocarbon components can reduce the self-shrinkage of concrete at all ages and reduce the porosity of concrete [27,28]. This shows that the admixture of an appropriate amount of nanoscale carbon-based materials in concrete can improve both conductivity and strength [29].…”
Section: Introductionmentioning
confidence: 92%
“…It is worth noting that research has also shown that cement mortar with the addition of NGPs has better acid resistance and durability. As shown in Figure 8, Farhan et al [151] prepared five mixes with the intrusion of NGPs (0%, 0.5%, 1.5%, 3%, and 5% by weight of cement) to study workability and mechanical properties. The compressive strength, tensile strength, and flexural strength of the sample containing 5% NGPs increased by 38.5%, 31.6%, and 44.34%, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 99%